Maternal high fat and/or salt consumption induces sex‐specific inflammatory and nutrient transport in the rat placenta. Issue 5 (19th May 2015) - Reynolds, Clare M.; Vickers, Mark H.; Harrison, Claudia J.; Segovia, Stephanie A.; Gray, Clint
Abstract: Maternal high fat and salt consumption are associated with developmental programming of disease in adult offspring. Inadequacies in placental nutrient transport may explain these 'programmed effects'. Diet‐induced inflammation may have detrimental effects on placental function leading to alteration of key nutrient transporters. We examined the effects of maternal high fat and/or salt diets on markers of placental nutrient transport and inflammation. Sprague–Dawley rats were assigned to (1) control (CD; 1% Salt 10% kcal from fat); (2) high salt (SD; 4% salt, 10% kcal from fat); (3) high fat (HF; 1% Salt 45% kcal from fat) or (4) high fat high salt (HFSD; 4% salt, 45% kcal from fat) 21 days prior to and throughout gestation. At embryonic day 18, dams were killed by isoflurane anesthesia followed by decapitation; placenta/fetuses were weighed, sexed, and collected for molecular analysis. Maternal SD, HF, and HFSD consumption decreased weight of placenta derived from male offspring; however, weight of placenta derived from female offspring was only reduced with maternal HF diet. This was associated with increased expression of LPL, SNAT2, GLUT1, and GLUT4 in placenta derived from male offspring suggesting increased fetal exposure to free fatty acids and glucose. Maternal SD, HF, and HFSD diet consumption increased expression of proinflammatory mediators IL‐1 β, TNF α, and CD68 in male placenta. Our results suggest that a proinflammatory placental profile results in detrimental alterations in nutrient transport which may contribute to the developmental origins of cardio‐metabolic disturbances in offspring throughout life. Abstract : There is considerable evidence regarding the contributory role of adverse fetal and early life nutritional environments to metabolic disease. The current study provides further evidence that increased maternal consumption of fat and salt independently and, for the first time, in combination, negatively impact placental and fetal growth and development thereby potentiating the risk for cardio‐metabolic disorders during later life.